Study on the Thermal Properties of Hollow Shale Blocks as Self-Insulating Wall Materials - Guo-liang Bai; Ning-jun Du; Ya-zhou Xu; Chao-gang Qin (Advances in Materials Science and Engineering)
To reduce energy consumption and protect the environment, a type of hollow shale block with 29 rows of holes was designed and produced. This paper investigated the thermal properties of hollow shale blocks and walls. First, the guarding heat-box method was used to obtain the heat transfer coefficient of the hollow shale block walls. The experimental heat transfer coefficient is 0.726 W/m2·K, which would save energy compared to traditional wall materials. Then, the theoretical value of the heat transfer coefficient was calculated to be 0.546 W/m2·K. Furthermore, the one-dimensional steady heat conduction process for the block and walls was simulated using the finite element analysis software ANSYS. The predicted heat transfer coefficient for the walls was 0.671 W/m2·K, which was in good agreement with the test results. With the outstanding self-insulation properties, this type of hollow shale block could be used as a wall material without any additional insulation measures in masonry structures.